Risk Management of Musyarakah Mutanaqisah Contract in Sharia Banks in Indonesia: Legal and Operational Issues - Ivan Rahmat Santoso; Molbi Harsanto; Ismet Sulila; Agil Bahsoan (International Journal of Applied Business and International Management, 2020)
This paper discusses how to solve problems occurring in the risk management of musyarakah mutanaqisah contract on home financing in sharia banks in Indonesia, particularly on its legal and operational issues. This study used a qualitative method using library data collection techniques and interviews. The study found that legal and operational risk management issues could be satisfactorily resolved by agreement of rescheduling, adding new conditions, and using new structures in accordance with Islamic teachings and applicable positive laws. In addition, ownership proof of some is needed to minimize the risk for the bank and the customer.